An Analysis of the Information-Seeking Behavior of Teachers in Special Education Institutes in Lahore: Needs, Practices and Challenges (International Journal of Politics & Social Sciences Review (IJPSSR), 2025)
The purpose of this article is to elucidate and analyze the information-seeking behavior of educators in special education institutions in Lahore. It aims to investigate the characteristics of information-seeking behavior and the obstacles that special education teachers encounter in accessing pertinent information. This research was conducted in four phases. In the initial phase, a comprehensive review of relevant literature was undertaken to comprehend the theoretical and methodological aspects of the study. The survey method was selected for data collection in the second phase. A questionnaire was adapted and administered to all respondents from public sector special education institutions (schools and colleges) in Lahore. The response rate was 44.6%. The questionnaire comprised 83 questions designed to identify specific facts relevant to the research. The total population size was 480, and the sample size was 214, as determined by the Morgan and Krejcie (1970) table for sample determination. A simple random sampling technique utilizing the lottery method was employed. 480 questionnaires were distributed, and the teachers were instructed to complete them manually, with 214 questionnaires submitted. In the third phase, the collected data were tabulated and analyzed to derive conclusions. In the final phase, conclusions were drawn, accompanied by recommendations. It was determined that special education teachers rely on specific sources and employ particular techniques for teaching, and their information needs differ from those of general education teachers.
Keywords: Special Education Teachers; Information Seeking Behavior; Challenges of Seeking Information